Surface structure errors on undergraduate students’ writing - Sari, Rita Karmila; Anggraeni, Ni Ketut Pertiwi (Aksara: Jurnal Bahasa dan Sastra, 2022)
Students will make an error in the process of acquiring a foreign language. Errors made by students in the process of learning need to be analyzed carefully so that it can help the learning process. This study aims to analyze the surface structure errors made by undergraduate students. The method used is a qualitative method which took a sample of 30 undergraduate students' writings which were writing assignments for English subject. The data were analyzed by looking at the taxonomy of the surface structure in 4 classifications, namely addition, omission, misformation, and misordering. The results of this study found that the most errors were misformation as much as 53%, followed by omissions as much as 23%, additions as much as 17% and misordering being the least errors found with a total of 7%. Misformation errors that often occurred in this study were in the tenses category where the use of morphemes was not in accordance with the rules of English grammar. The results show common errors made by undergraduate students and are expected to be a benchmark for learning outcomes. In addition, it can also show what indicators of English learning should be improved so that students no longer make repeated errors.